Numerical parametric simulations for seepage flow behaviour through an earthfill dam - Kasim, Fauziah; Wong, Sou Fei (Faculty of Civil Engineering, 2002)

(untitled)
A finite element method is practical and applicable for many fields including for geotechnical engineering structures. Seepage through earth dam is difficult to analyse especially dams with multiple zones. Therefore, finite element is the best tool for analyzing seepage flow in an earthfill dam. The main objective of the project is to simulate the seepage flow through an earthfill dam. Three sets of steady state numerical modeling are presented in the paper. Two sets of parametric studies on long-term steady state flow were conducted using homogeneous and zoned earthfill dams for studying the behaviour of seepage in the dams. The third set of the simulations is a case study, which is analysis of steady state seepage condition for Kuala Yong Dam, the main part of Pergau Hydroelectric Project, Tenaga Nasional Berhad (TNB). The seepage quantity at the core and the downstream section were determined for the steady state flow condition. The results of the parametric simulations show that the total fluxes at downstream changes with the coefficient of permeability value. The flux quantity changes linearly with maximum seepage velocity. Significant differences can be observed in the case study, for the analysis using the coefficient of permeability function (varies with matric suction) versus analysis using a constant coefficient of permeability. Relationship between flux quantity at downstream and maximum seepage velocity is non-linear when hydraulic conductivity function is introduced in seepage analysis